The evolution of online extensive reading and web-based platforms in EFL/ESL: A narrative review of impacts, challenges, and future directions - Amine Ounissi; Raihana Romly; Azza Jauhar Ahmad Tajuddin; Md. Kamrul Hasan (Australian Journal of Applied Linguistics)
Engagement in extensive reading (ER) on the Internet provides learners with unparalleled access to diverse digital resources, positioning Online Extensive Reading (OER) as a transformative extension of traditional ER practices. OER combines the principles of ER with the affordances of modern technology, offering interactivity, multimedia features, and adaptive tools that foster reading proficiency, vocabulary growth, and motivation. This paper thoroughly reviews OER’s development and its impact on EFL/ESL education over the past decade (2014–2024), analysing 43 peer-reviewed studies from Scopus and Web of Science. Adopting a narrative review methodology, this study utilises a structured literature matrix to synthesise findings, critically analyse, and evaluate key data from diverse research studies, offering a comprehensive understanding of OER’s pedagogical implications. Findings demonstrate that OER significantly enhances learner engagement and autonomy, particularly when integrated with interactive platforms. However, challenges, such as inadequate technical support, progress tracking difficulties, and digital literacy disparities hinder its full potential. To address these barriers, this paper advises policymakers to strengthen digital infrastructure, invest in digital literacy programs, and provide ongoing professional development for educators. Expanding access to graded online reading materials and overcoming these challenges enables OER to integrate effortlessly into modern educational ecosystems, enhancing language-learning outcomes, fostering engagement, and promoting autonomy in digital environments.